Local atomic structure and oxidation processes of Cu(I) binding site in amyloid beta peptide: XAS Study. (May 2016) - Kremennaya, M A; Soldatov, M A; Stretsov, V A; Soldatov, A V
Abstract: There are two different motifs of X-ray absorption spectra for Cu(I) K-edge in amyloid-β peptide which could be due to two different configurations of local Cu(I) environment. Two or three histidine ligands can coordinate copper ion in varying conformations. On the other hand, oxidation of amyloid-β peptide could play an additional role in local copper environment. In order to explore the peculiarities of local atomic and electronic structure of Cu(I) binding sites in amyloid-β peptide the x-ray absorption spectra were simulated for various Cu(I) environments including oxidized amyloid-β and compared with experimental data.